Interfacial passivation with 4-chlorobenzene sulfonyl chloride for stable and efficient planar perovskite solar cells - Foo, Shini (2022)
The interfacial passivation technique is an effective method to improve the stability and photovoltaic performance of perovskite solar cells. Here, we demonstrate the importance of passivating undercoordinated halide ions in minimizing carrier losses at the perovskite/spiro-OMeTAD interface. 4-Chlorobenzene sulfonyl chloride (CBSC) has been utilized as a Lewis acid passivation material. CBSC molecules act as electron acceptors, which bind to the negatively charged undercoordinated halide ions and Pb-I antisite defects (PbI3−). The champion CBSC-passivated perovskite device shows a high power conversion efficiency (PCE) of 20.02%, unlike the pristine device with an efficiency of 18.29%. Significant long term-stability in the CBSC passivated device is also observed, maintaining 93% of the initial PCE after 768 h stored in ambient conditions with 30% relative humidity.